Response of the organellar and nuclear (post)transcriptomes of Arabidopsis to drought - Xu, Duorong; Tang, Qian; Xu, Ping; Schäffner, Anton R.; Leister, Dario; Kleine, Tatjana (Frontiers in Plant Science, 2023)
Plants have evolved sophisticated mechanisms to cope with drought, which involve massive changes in nuclear gene expression. However, little is known about the roles of post-transcriptional processing of nuclear or organellar transcripts and how meaningful these changes are. To address these issues, we used RNA-sequencing after ribosomal RNA depletion to monitor (post)transcriptional changes during different times of drought exposure in Arabidopsis Col-0. Concerning the changes detected in the organellar transcriptomes, chloroplast transcript levels were globally reduced, editing efficiency dropped, but splicing was not affected. Mitochondrial transcripts were slightly elevated, while editing and splicing were unchanged. Conversely, alternative splicing (AS) affected nearly 1,500 genes (9% of expressed nuclear genes). Of these, 42% were regulated solely at the level of AS, representing transcripts that would have gone unnoticed in a microarray-based approach. Moreover, we identified 927 isoform switching events. Our data show that AS enhances proteome diversity to counteract drought stress and represent a valuable resource that will facilitate the development of new strategies to improve plant performance under drought. We provide a table of the most interesting candidates, and as proof of principle, increased drought tolerance of the carbonic anhydrase ca1 and ca2 mutants is shown. In addition, altering the relative contributions of the spliced isoforms could increase drought resistance. For example, our data suggest that the accumulation of a nonfunctional FLM (FLOWERING LOCUS M) isoform and not the ratio of FLM-ß and -δ isoforms may be responsible for the phenotype of early flowering under long-day drought conditions.